COHESION AND COHERENCE IN THESES WRITTEN BY UNDERGRADUATE STUDENTS OF THE ENGLISH DEPARTMENT AT THE UNIVERSITY OF MATARAM - Nur Fitriyanti Aspany; Untung Waluyo; Nawawi Nawawi (Program Studi Pendidikan Bahasa Inggris, 2021)
The issue of cohesion and coherence has long been recognized as a serious problem among students of English who write theses. However, it remains unresolved up to now. This present study aims to analyze the cohesion and coherence contained in students’ theses based on the theoretical constructs developed by Halliday & Hasan (1976) and Oshima & Hogue (2006). The study employs a descriptive qualitative approach. The data were taken from the top 8 selected theses written by undergraduate students of the English department at the University of Mataram. The data taken from the students’ thesis manuscripts were categorized and analyzed based on the aforementioned theoretical perspectives. Results of the analysis show on the whole students’ theses under investigation generated four issues related to the use of cohesion and coherence. The first issue dealt with the use of grammatical cohesion and lexical cohesion. The second issue contained errors in the use of cohesion devices and lexicon. The third was related to discrete coherence such as repeating key nouns, using consistent pronouns, using transition signals, and arranging ideas in logical order also found in the thesis. Fourth, incoherent theses were found because of misused repeating key nouns, inconsistent pronouns, and transition signals used. Thus, all aspects of cohesion and coherence in theses found in the theses but not comprehensive.